KEANEKARAGAMAN JENIS KUPU-KUPU LEPIDOPTERA DISEKITAR KAMPUS UNIVERSITAS SAN PEDRO, KOTA KUPANG NUSA TENGGARA TIMUR - Fahik, Mery; Lodo Rame, Agustina (Universitas Cokroaminoto Palopo, 2025)
The objective of this study is to identify butterfly species within the vicinity of Universitas San Pedro. The research was conducted across the university campus, utilizing roaming and point count methods at four designated stations. The Lepidoptera butterfly species diversity at Universitas San Pedro encompasses Nymphalidae, comprising 11 species totaling 111 individuals, along with Pieridae with 6 species and 54 individuals, Papilionidae with 5 species and 40 individuals, Lycaenidae with 3 species and 20 individuals, and Hesperidae with 2 species and 16 individuals. The average Lepidoptera butterfly diversity index is 3.202, indicating a high level of diversity, along with an evenness index of 0.972, signifying uniformity and stability within the Lepidoptera butterfly community surrounding Universitas San Pedro. Conversely, the average dominance index of 0.044 denotes a low dominance of Lepidoptera butterfly species within the area